The Dynamics of Stress and Discipline as Determining Factors of Job Satisfaction for Educators (A Case Study at SMK NU Miftahul Falah Kudus) (Pascasarjana IAIN Kudus, 2024)
This study aims to analyze the effect of work stress and work discipline on job satisfaction of educators at SMK NU Miftahul Falah Kudus. The research method used is quantitative with a descriptive approach and multiple regression analysis. Data were collected through questionnaires distributed to the entire population of educators, a total of 33 respondents. The results showed that work discipline has a positive and significant effect on job satisfaction with a significance value of 0.033 < 0.05 and a regression coefficient of 0.369. Work stress has a negative and significant effect on job satisfaction with a significance value of 0.025 < 0.05 and a regression coefficient of -0.351. In addition, work stress and work discipline together have a significant effect on job satisfaction with a significance value of 0.001 < 0.05 and an R² value of 0.353. At the same time, both variables contribute 35.3% to the educators' job satisfaction. Although the level of work discipline is relatively high, job satisfaction still needs improvement, especially in the aspects of salary and financial benefits. This study recommends better stress management, strengthening the culture of discipline, and reviewing the compensation system to support educators' well-being and optimal performance.